IFN-β Acts on Monocytes to Ameliorate CNS Autoimmunity by Inhibiting Proinflammatory Cross-Talk Between Monocytes and Th Cells - Rasouli, Javad; Casella, Giacomo; Ishikawa, Larissa L. W.; Thome, Rodolfo; Boehm, Alexandra; Ertel, Adam; Melo-Silva, Carolina R.; Mari, Elisabeth R.; Porazzi, Patrizia; Zhang, Weifeng; Xiao, Dan; Sigal, Luis J.; et al. (Frontiers in Immunology, 2021)
IFN-beta has been the treatment for multiple sclerosis (MS) for almost three decades, but understanding the mechanisms underlying its beneficial effects remains incomplete. We have shown that MS patients have increased numbers of GM-CSF+ Th cells in circulation, and that IFN-beta therapy reduces their numbers. GM-CSF expression by myelin-specific Th cells is essential for the development of experimental autoimmune encephalomyelitis (EAE), an animal model of MS. These findings suggested that IFN-beta therapy may function via suppression of GM-CSF production by Th cells. In the current study, we elucidated a feedback loop between monocytes and Th cells that amplifies autoimmune neuroinflammation, and found that IFN-beta therapy ameliorates central nervous system (CNS) autoimmunity by inhibiting this proinflammatory loop. IFN-beta suppressed GM-CSF production in Th cells indirectly by acting on monocytes, and IFN-beta signaling in monocytes was required for EAE suppression. IFN-beta increased IL-10 expression by monocytes, and IL-10 was required for the suppressive effects of IFN-beta. IFN-beta treatment suppressed IL-1b expression by monocytes in the CNS of mice with EAE. GM-CSF from Th cells induced IL-1b production by monocytes, and, in a positive feedback loop, IL-1b augmented GM-CSF production by Th cells. In addition to GM-CSF, TNF and FASL expression by Th cells was also necessary for IL-1b production by monocyte. IFN-beta inhibited GM-CSF, TNF, and FASL expression by Th cells to suppress IL-1b secretion by monocytes. Overall, our study describes a positive feedback loop involving several Th cell- and monocyte-derived molecules, and IFN-beta actions on monocytes disrupting this proinflammatory loop.